Consolidating role of the self-regulating organizations IN BUSINESS DEVELOPMENT (Путеводитель предпринимателя)
In work it is proved that for creation of a real resource reserve of the organization full and unconditional performance of tasks in view on increase of power efficiency of all industrial and housing-and-municipal complexes, all-round studying of principles and methods of realization of problems in the field of power efficiency in regions is necessary. The special attention in article is given interrelation between cluster to the self-regulating organization in the field of power audit, the power service companies and the enterprises of a power effective orientation, sources of their financing.